2019
DOI: 10.1063/1.5125758
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of coherent structures in two-dimensional turbulent Rayleigh-Bénard convection

Abstract: Characterization of coherent structures in turbulent Rayleigh-Bénard convection using statistical measures is presented in the present work. Numerical simulations are carried out in a two-dimensional (2D) rectangular cell with aspect ratio 2 using air as the working fluid across four decades of Rayleigh number. The absence of one lateral dimension leads to entrapment of plumes which are consequently emitted in the form of thermal jets. Axial nonuniformity in thermal boundary layers is eliminated at high Raylei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…The volume-time-averaged contributions of A K , T K and P S being negligible result in an exact balance between global buoyancy production (P B ) and turbulent dissipation ( ). In table 2, a direct comparison is made between the present rough case and the smooth surface case (Chand et al 2019) for volume-time-averaged P B , and the Nusselt number. Note that in the present roughness configuration, there is a slight digression from the expected balance between the global P B and .…”
Section: Heat Transport Mechanismmentioning
confidence: 99%
See 3 more Smart Citations
“…The volume-time-averaged contributions of A K , T K and P S being negligible result in an exact balance between global buoyancy production (P B ) and turbulent dissipation ( ). In table 2, a direct comparison is made between the present rough case and the smooth surface case (Chand et al 2019) for volume-time-averaged P B , and the Nusselt number. Note that in the present roughness configuration, there is a slight digression from the expected balance between the global P B and .…”
Section: Heat Transport Mechanismmentioning
confidence: 99%
“…It can be observed that with increase in δ, the scaling exponents for both V pl and pl increase in absolute sense, while for V bg and bg , they appear to be more stable. Further, to explain how roughness alters plume regions, variation of V pl and pl with Ra is compared with the smooth surface case (Chand et al 2019) for δ = 1 % and 5 % in figure 7. It is clear that irrespective of δ, both V pl and pl are higher for the roughened surface with slower decay over increasing Ra.…”
Section: Plume Statisticsmentioning
confidence: 99%
See 2 more Smart Citations
“…The coherent vortices carry the high-momentum fluid from the main channel into the shallow floodplains, thereby enhancing the transverse scalar and momentum exchange. Previous studies show that the horizontal coherent vortices can be also detected at the confluence of two rivers (Uijttewaal & Booij, 2000;Yuan et al, 2016), in the turbulent Rayleigh-Benard convection (Chand et al, 2019), around the groynes of a trapezoidal open channel (Zhang et al, 2019), as well as in the wakes of an island (Alaee et al, 2007). Recently, Juez et al (2019) conducted a comprehensive study in an open asymmetric compound channel to investigate the large vortical structures and mass exchange near the mixing interface under different channel characteristics.…”
mentioning
confidence: 99%